2004
DOI: 10.1175/jam2168.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Vertical Soundings and Sidewall Air Temperature Measurements in a Small Alpine Basin

Abstract: Tethered balloon soundings from two sites on the floor of a 1-km-diameter limestone sinkhole in the eastern Alps are compared with pseudovertical temperature “soundings” from three lines of temperature dataloggers on the basin's northwest, southwest, and southeast sidewalls. Under stable nighttime conditions with low background winds, the pseudovertical profiles from all three lines were good proxies for free air temperature soundings over the basin center, with a mean nighttime cold temperature bias of about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 9 publications
1
32
0
Order By: Relevance
“…It follows that the temperature difference between the top and the bottom of the ABL is well estimated by the difference in temperature between any high-elevation station and any lowelevation station, and that the latter may be indicative of the ABL static stability. This is consistent with the results of Whiteman et al (2004) who have shown that temperature vertical profiles can be well-approximated by pseudovertical profiles obtained from temperature stations on the sidewalls, in strongly stable and low synoptic wind conditions.…”
Section: Methodssupporting
confidence: 92%
“…It follows that the temperature difference between the top and the bottom of the ABL is well estimated by the difference in temperature between any high-elevation station and any lowelevation station, and that the latter may be indicative of the ABL static stability. This is consistent with the results of Whiteman et al (2004) who have shown that temperature vertical profiles can be well-approximated by pseudovertical profiles obtained from temperature stations on the sidewalls, in strongly stable and low synoptic wind conditions.…”
Section: Methodssupporting
confidence: 92%
“…It is difficult to accurately estimate the inversion strength and depth of the near-surface cold pools in the MDVs because vertical profile observations during winter are unavailable. Whiteman et al (2004) demonstrate that valley sidewall temperatures can be used in place of freeair vertical profile measurements under clear and stable conditions. Accordingly, comparisons of temperatures on the valley sidewalls in the MDVs to those on the valley floor would suggest that cold pooling may be in the order of ;108C in the Taylor Valley [Lake Fryxell (TF); Lake Bonney (TB)], ;158C in the Wright Valley [Lake Vanda (WV)], and ;208C in the Victoria Valley (VV).…”
Section: B Local Meteorological Observationsmentioning
confidence: 89%
“…6). This is a combination of forced channeling owing to the westerly component of the upstream flow but also pressure-driven channeling (see Whiteman and Doran 1993) To isolate the synoptic configuration associated with foehn in the MDVs, composites of SLP field and wind vectors for 2006 and 2007 were constructed based on 172 foehn days recorded at three or more valley surface stations, compared to the 172 nonfoehn days. There were 398 total nonfoehn days through 2006 and 2007, 172 were selected to match the sample number of foehn days.…”
Section: Modeled Foehn Dynamicsmentioning
confidence: 99%
“…Whiteman et al (2004b) conducted vertical soundings and sidewall air temperature measurements in a limestone sinkhole (valley) in karst plateau on Hetzkogel (Austria).…”
Section: Introductionmentioning
confidence: 99%